Internal retraction in single-port laparoscopic cholecystectomy: Initial experience and learning curve. Issue 3 (June 2013) - Steinemann, Daniel C.; Limani, Perparim; Clavien, Pierre-Alain; Breitenstein, Stefan
Abstract Introduction: We report our experience and learning curve in single-port laparoscopic cholecystectomy (SPLC) using an internal anchored retraction system. Methods: Usefulness of the retraction system was analysed in 18 SPLC. The first eight, the following ten SPLC and 20 consecutive four-port laparoscopic cholecystectomies (4PLC) were compared. Duration of operation, burns on nontarget tissue and gallbladder perforations were assessed by reviewing videotapes recorded during the procedures. Results: Use of the retraction system failed in three out of five patients (60%) with intraoperative signs of chronic inflammation and in one out of 13 (7.1%) without such signs (p = 0.0441). Median operation time was 90 (45–120) in the first eight and 55 (40–180) minutes in the following ten SPLC (p = 0.0361). Whereas the first eight SPLC lasted longer compared to 4PLC (70 (40–140) minutes, p = 0.0435) the difference disappeared after eight procedures (p = 0.2076). Median number of burns to nontarget tissue was seven (1–16) in the first eight and one (0–8) in the following ten SPLC (p = 0.0049). There was no difference in perforation of the gallbladder. Discussion: Internal retraction enables a safe exposure of the Calot triangle avoiding bile spillage in cholecystectomies without intraoperative signs of inflammation. Familiarisation with SPLC was rapidly achieved. Operation time and dexterity were equal to 4PLC after eight SPLC.